KOLABORASI MAHASISWA KKL IAI PADANG LAWAS DAN MASYARAKAT DESA ULU AER DALAM MELAWAN BAHAYA NARKOBA DAN KDRT - Ismail Nasution; Maryam Zakiyah Gulo; Amna Sari Lubis; Syawal Hadi Hasibuan; Mhd. Riyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the collaboration between IAI Padang Lawas Field Work Lecture (KKL) students and the Ulu Aer Village community in an effort to prevent the dangers of drugs and domestic violence (KDRT). The research approach used is descriptive qualitative through observation, interviews, and documentation of activities. The results show that this collaboration is realized in the form of socialization, legal counseling, anti-drug campaigns, and skills training as an alternative to strengthen the family economy. Obstacles faced include a lack of awareness among some members of the community and limited resources. In conclusion, the synergy between students and the community has proven effective in increasing collective awareness of the dangers of drugs and domestic violence in Ulu Aer Village.